Crystal structure of (4-(4-isopropylphenyl)-1H-pyrrol-3-yl)(ferrocenyl)methanone, C24H23FeNO - Tian Hangzhou; Chen Geyu; Ma Jiejie; Liu Bin (Zeitschrift für Kristallographie - New Crystal Structures)
C24H23FeNO, monoclinic, P21/c (no. 14), a = 15.4240(10) Å, b = 10.2113(7) Å, c = 12.2776(7) Å, β = 105.808(2)°, V = 1860.6(2) Å3, Z = 4, Rgt(F) = 0.0564 wRref(F2) = 0.1804, T = 170 K.